Changing Patterns of Household Expenditures on Energy : A Case Study of Indonesia and Pakistan - Bacon, Robert (World Bank, Washington, DC, 2014)
This paper applies a decomposition technique using a log mean Divisia index to two sets of household surveys taken several years apart in Indonesia and Pakistan. The methodology enables separation of changes in expenditure on different types of energy into changes in prices, quantities, the share of households using the given form of energy, and total household income. The technique was applied to electricity, liquefied petroleum gas (LPG), kerosene, and gasoline in Indonesia, and to natural gas, kerosene, LPG, purchased firewood, collected firewood, dung cake, and other forms of biomass in Pakistan. The methods of analysis presented in this paper could be extended to other commodities or to changes in energy use patterns over longer periods of time, where suitable household expenditure surveys are available. In particular, when household surveys covering the period of high oil prices become available, the analysis of changing household patterns of fuel use will be valuable. The availability of evidence on the use of energy by various household groups will be important for considerations of providing targeted support to low-income households at times of unexpected shocks to energy prices.